Pharmacological Inhibition of Inositol-Requiring Enzyme 1α RNase Activity Protects Pancreatic Beta Cell and Improves Diabetic Condition in Insulin Mutation-Induced Diabetes - Herlea-Pana, Oana; Eeda, Venkateswararao; Undi, Ram Babu; Lim, Hui-Ying; Wang, Weidong (Frontiers in Endocrinology, 2021)
β-cell ER stress plays an important role in β-cell dysfunction and death during the pathogenesis of diabetes. Proinsulin misfolding is regarded as one of the primary initiating factors of ER stress and unfolded protein response (UPR) activation in β-cells. It is unknown whether targeting ER stress/UPR can ameliorate diabetes and protect β-cells. Here, we found that the ER stress sensor inositol-requiring enzyme 1 (IRE1) was activated in the Akita mice, a mouse model of mutant insulin gene-induced diabetes of youth (MIDY), a monogenic diabetes. Normalization of IRE1 RNase hyperactivity by pharmacological inhibitors significantly ameliorated the hyperglycemic conditions and increased serum insulin levels in Akita mice. These benefits were accompanied by a concomitant protection of functional β-cell mass, as shown by the suppression of β-cell apoptosis, increase in mature insulin production and reduction of proinsulin level. At the molecular level, we observed that the expression of genes associated with β-cell identity and function was significantly up-regulated and ER stress and its associated inflammation and oxidative stress were suppressed in islets from Akita mice treated with IRE1 RNase inhibitors. This study provides the first evidence of the in vivo efficacy of IRE1 RNase inhibition in Akita mice, pointing to the possibility of targeting IRE1 RNase as a therapeutic direction for the treatment of diabetes.